Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy - Tishechkin, Dmitri Yu. (Zootaxa, 2018)
Investigation of morphological variability in three species of Central-Asiatic Idiocerinae showed that small differences in the shape of male genitalia and abdominal apodemes are not species-specific traits. Based on these data, the following synonymies are established: Populicerus ambigenus (Dubovskiy, 1966) = P. tenellus (Dubovskiy, 1966), syn. n., Idiocerus bilituratus Dubovskiy, 1966 = I. bipustulatus Mityaev, 1967, syn. n.; the synonymy Sahlbergotettix salicicola (Flor, 1861) = S. mesasiaticus Dubovskiy, 1966 = Idiocerus fulvius Dlabola, 1967 established by Anufriev (1978) is confirmed. Illustrated descriptions of three species considered and data on their male calling signals, biology, and distribution are provided.